2022
DOI: 10.1002/cl2.1215
|View full text |Cite
|
Sign up to set email alerts
|

Opioid‐specific medication‐assisted therapy and its impact on criminal justice and overdose outcomes

Abstract: Background: The overlap between justice system involvement and drug use is welldocumented. Justice-involved people who misuse opioids are at high risk for relapse and criminal recidivism. Criminal justice policymakers consider opioid-specific medication-assisted therapies (MATs) one approach for improving outcomes for this population. More research is needed that explores the impacts of opioid-specific MATs for justice-involved people.Objectives: This study sought to assess the effects of opioid-specific MAT f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 91 publications
(119 reference statements)
0
0
0
Order By: Relevance
“…After systematically reviewing 20 CLS-based MOUD studies, Strange and colleagues found that provision of MOUD in these settings was associated with a significantly reduced the risk of non-fatal opioid overdose following release but not with reduced risk of fatal overdose or recidivism. The authors suggested the null effect on fatal overdoses could be due to difficulty in accessing mortality records [ 14 ]. and highlighted the need for more rigorous research in this area, including the use of experimental designs.…”
Section: Introductionmentioning
confidence: 99%
“…After systematically reviewing 20 CLS-based MOUD studies, Strange and colleagues found that provision of MOUD in these settings was associated with a significantly reduced the risk of non-fatal opioid overdose following release but not with reduced risk of fatal overdose or recidivism. The authors suggested the null effect on fatal overdoses could be due to difficulty in accessing mortality records [ 14 ]. and highlighted the need for more rigorous research in this area, including the use of experimental designs.…”
Section: Introductionmentioning
confidence: 99%